PENERAPAN KAPITALISASI SEWA TERHADAP MANAJEMEN LABA - Sita Ayu Samsiah; Ayunita Ajengtiyas Saputri Mashuri (Media Riset Akuntansi, Auditing & Informasi, 2023)
This study aims to find out the effect of applying the mandatory capitalization lease on the application of PSAK 73 to earnings management practices. This quantitative study research uses secondary data on annual financial reports for all companies listed on the Indonesia Stock Exchange for the 2018-2021 period with the criteria for these companies disclosing an operating lease commitment and reporting minimum lease payments in the Notes to Financial Statements (CALK). The final total sample of companies is 37 companies with a total sample of 148. The data analysis technique in this study uses multiple linear regression using panel data regression and also uses a different test for the second hypothesis in this study where the data processing program used is software STATA v. 16. Based on the research results, it is found that the capitalization of leases proxied by lease liabilities has a significant negative effect on earnings management. Based on the results of the Wilcoxon test there are differences between before and after the application of capitalization leases to earnings management.